MANAJEMEN PERPUSTAKAAN DALAM MENUNJANG MUTU PENDIDIKAN DI MI AL HASIB PAKIS MALANG PAKIS MALANG - Armi Nata Kusuma; Ika Ratih Sulistiani; Lia Nur Atiqoh Bela Dina (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
Madrasah Ibtidaiyah Tarbiyyatul Arifin Malang is one of the schools located in the Pakistani district, more precisely in the Pakisjajar area. The school is located on a main road that is easily accessible to people. MI Al Hasib Pakis Malang Pakis Malang has a school library. MI Al Hasib Library Pakis Malang Pakis Malang has just started a pioneering again, because previously the library had experienced a few months before that. Therefore, researchers focus more on library management planning, implementation and evaluation at MI Al Hasib Pakis Malang. And the second focus is the role of libraries in MI Al Hasib Pakis Malang, Malang ferns. This study uses data collection techniques such as observation, interviews and documentation. From this study, researchers explain about library management at MI Al Hasib Pakis Malang Pakis Malang, which includes planning, implementation and evaluation activities. while in the role of the library, there is a library as a learning center, the library is a collection of books, and the library can foster student interest in reading so that the library can improve the quality of education at MI Al Hasib Pakis Malang. Keywords: management, library, quality of education